The Influence sharaf lasson of Drill Method on Tashrif Istilahy Mastery at the Eighth Grade Junior High School Students Darul Hikmah Pekanbaru. - Daulay, Desya Indah Marwiyah; Amrizal, Amrizal; Aoyama, Tosyiko (Al-Manar, 2024)
This study is experimental research which aims to find out whether there is a significant influence on the use of drill method on Tashrif Istilahy mastery at the eighth grade junior high school students Darul Hikmah Pekanbaru. The problem formulation in this research is “Is there any significant influence on the use of drill method on Tashrif Istilahy mastery at the eighth grade junior high school students Darul Hikmah Pekanbaru?”The population of this study is all students of class VIII junior high school Darul Hikmah Pekanbaru, with a sample of class VIII.H female students as experimental class and class VIII.F students as the control class. Subject of this research is all VIII students of junior high school Darul Hikmah Pekanbaru. The object of this research is the influence on the use of drill method on Tashrif Istilahy mastery at the eighth grade junior high school students Darul Hikmah Pekanbaru. The instruments use the collecting data which consists of observations and tests. The result of analysis data can be concluded that there is no significant influence with the use of the drill method on Tashrif Istilahy mastery at the eighth grade junior high school students Darul Hikmah Pekanbaru. This is proven by the value to= 0.66 which is smaller than tt at 1% significance level = 2.72 and 5% significance level = 2.02 so Ho is accepted and Ha is rejected, which means the drill method has no effect on Tashrif Istilahy mastery at the eighth grade junior high school students students Darul Hikmah Pekanbaru.Keywords: Influence, Drill Method, Tashrif Istilahy